Job satisfaction within kindergartens of Hjallastefnan : the perspective of employees towards factors affecting their job satisfaction - Harpa Vilborg R. Schram 1996- (2020)
Job satisfaction matters for employees of an organization but also for the organization as a whole. Various factors affect job satisfaction and the purpose of the study was to examine the perspective of employees within kindergartens of Hjallastefnan towards factors affecting their job satisfaction. The study was conducted at six kindergartens of Hjallastefnan within the capital area of Iceland. The design was twofold as both qualitative and quantitative methods were used. Semi-structured interviews were used to interview the six kindergarten principals and a questionnaire was sent to other employees of the kindergartens in which a total of 69 employees participated out of a 156 employee sample group. The results showed that the overall employee morale was good, most participants were satisfied with their supervisors and co-workers as well as other factors concerning the work conditions such as shortening of working hours. The kindergarten principals‘ ideas about the operations of the kindergartens and how they affect their employees were mostly consistent with the satisfaction of their employees. The results of the study can be used to improve certain factors in order to increase job satisfaction even more as well as recognizing those operations that work well. Keywords: job satisfaction, kindergartens, factors, work conditions Starfsánægja skiptir máli fyrir starfsmenn innan fyrirtækis en hún skiptir einnig máli fyrir fyrirtækið í heild sinni. Margir ólíkir þættir hafa áhrif á starfsánægju en markmið rannsóknarinnar var að skoða viðhorf starfsmanna leikskóla Hjallastefnunnar til þátta sem hafa áhrif á starfsánægju þeirra. Rannsóknin var framkvæmd innan sex leikskóla Hjallastefnunnar á höfuðborgarsvæðinu. Rannsóknarsniðið var tvenns konar þar sem gagnasöfnun fór fram bæði með eigindlegum og megindlegum aðferðum. Viðtöl voru tekin við sex leikskólastjóra og þá var spurningalisti sendur til annarra starfsmanna leikskólanna sem samtals 69 starfsmenn svöruðu af 156 manna úrtaki. Niðurstöðurnar sýndu að ...